Tìm x, biết:
a) 2 + x = 6
b) [(2 - 2) . 9 + x = [6 : (1 + 2 + 3 )]
Tìm x biết:
a) x(x - 2) - x2 + 5x = 6
b) (x - 3)2 - x + 9 =0
giúp mình câu này nha
\(a,\Leftrightarrow x^2-2x-x^2+5x=6\\ \Leftrightarrow3x=6\\ \Leftrightarrow x=2\)
\(b,\Leftrightarrow x^2-6x+9-x+9=0\\ \Leftrightarrow x^2-7x+18=0\\ \Leftrightarrow\left(x^2-7x+\dfrac{49}{4}\right)+\dfrac{23}{4}=0\\ \Leftrightarrow\left(x-\dfrac{7}{2}\right)^2+\dfrac{23}{4}=0\left(vôlí\right)\)
Tìm x, biết:
a) x(5 + 3x) – (x + 1)(3x – 2) = 6
b) (2x + ½ )² – (1 – 2x)² = 2
c) x(x + 3) – 2x – 6 = 0
\(a,\Rightarrow5x+3x^2-3x^2-x+2=6\\ \Rightarrow4x=4\Rightarrow x=1\\ b,\Rightarrow\left(2x+\dfrac{1}{2}-1+2x\right)\left(2x+\dfrac{1}{2}+1-2x\right)=2\\ \Rightarrow\dfrac{3}{2}\left(4x-\dfrac{1}{2}\right)=2\\ \Rightarrow6x-\dfrac{3}{4}=2\\ \Rightarrow6x=\dfrac{11}{4}\\ \Rightarrow x=\dfrac{11}{24}\\ c,\Rightarrow\left(x+3\right)\left(x-2\right)=0\\ \Rightarrow\left[{}\begin{matrix}x=2\\x=-3\end{matrix}\right.\)
Tìm x biết:
a) 5x.(x-1)-(x+2).(5x-7)=6
b) (x+2)2-(x2-4)=0
`a)5x(x-1)-(x+2)(5x-7)=6`
`<=>5x^2-5x-(5x^2-7x+10x-14)=6`
`<=>5x^2-5x-(5x^2+3x-14)=6`
`<=>-8x+14=6`
`<=>8x=8<=>x=1`
Vậy `x=1`
`b)(x+2)^2-(x^2-4)=0`
`<=>x^2+4x+4-x^2+4=0`
`<=>4x+8=0`
`<=>4x=-8`
`<=>x=-2`
Vậy `x=-2`
a)5x.(x-1)-(x+2).(5x-7)=6
<=> 5x2-5x-(5x2-7x+10x-14)=6
<=> 5x2-5x-5x2+7x-10x+14=6
<=> -8x+14=6
<=> -8x=-8 => x=1
Vậy x=1
b) (x+2)2-(x2-4)=0
<=> (x+2)2-(x2-22)=0 <=> (x+2)2-(x-2)(x+2)=0
<=> (x+2)[(x+2)-(x-2)]=0
<=> (x+2)(x+2-x+2)=0
<=> (x+2).4=0
=> x+2=0
=> x=-2
Vậy x=-2
Tìm x biết:
a) -3/4 = x/20
b) - (-6)/12 - x = 9/48
c)3/5 - ( 2 và 1/5 - x) 2= 6/25
tìm x, biết:
a, x:3.5=3/4 :-5/6
b,x-1.2/2 = 8/x-1.2
`x :3*5 = 3/4 :(-5/6)`
`x :15 =3/4*(-6/5)=-9/10`
`x = -9/10 *15 =-27/2`
`x-1*2/2 = 8/x -1.2`
`x- 1*1 = 8/x -2`
`x-8/x = -2+1`
`x-8/x =-1`
`x^2 -8x =-x`
`x^2 -8x +x=0`
`x^2 -7x =0`
`x(x-7) =0`
`=>[(x=0),(x=7):}`
`a, x \div 15=-9/10`
`x=-9/10*14`
`x=-27/2`
`b, (x-1*2)/2=8/(x-1*2)`
\(\left(x-1\cdot2\right)\cdot\left(x-1\cdot2\right)=8\cdot2\)
`(x-1*2)^2=16`
`(x-1*2)^2=(+-4)^2`
\(\Rightarrow\left[{}\begin{matrix}x-1\cdot2=4\\x-1\cdot2=-4\end{matrix}\right.\)
`=>`\(\left[{}\begin{matrix}x-2=4\\x-2=-4\end{matrix}\right.\)
`=>`\(\left[{}\begin{matrix}x=4+2\\x=\left(-4\right)+2\end{matrix}\right.\)
`=>`\(\left[{}\begin{matrix}x=6\\x=-2\end{matrix}\right.\)
Bài 3:Tìm các số nguyên x,biết:
a)(2 x - 5)+17=6
b)10 - 2( 4 - 3 x ) = - 4
c)10 - 2( 4 - 3 x ) = - 4
d)5 - 2 x = - 17 + 12
\(a,2x-5+17=6\\ \Rightarrow2x=-6\\ \Rightarrow x=-3\\ b,\Leftrightarrow10-8+6x=-4\\ \Leftrightarrow6x=-6\Leftrightarrow x=-1\\ d,\Rightarrow-2x=-10\\ \Rightarrow x=5\)
câu c giống câu b nhó
tìm x, biết:
a) x2-2x+1=25
b) (5x+1)2-(5x-3)(5x+3)=30
c) (x-1)(x2+x+1)-x(x+2)(x-2)=5
d) (x-2)3-(x-3)(x2+3x+9)+6(x+1)2=15
a) Ta có: \(x^2-2x+1=25\)
\(\Leftrightarrow\left(x-1\right)^2=25\)
\(\Leftrightarrow\left[{}\begin{matrix}x-1=5\\x-1=-5\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=6\\x=-4\end{matrix}\right.\)
b) Ta có: \(\left(5x+1\right)^2-\left(5x-3\right)\left(5x+3\right)=30\)
\(\Leftrightarrow25x^2+10x+1-25x^2+9=30\)
\(\Leftrightarrow10x=20\)
hay x=2
c) Ta có: \(\left(x-1\right)\left(x^2+x+1\right)-x\left(x+2\right)\left(x-2\right)=5\)
\(\Leftrightarrow x^3-1-x\left(x^2-4\right)=5\)
\(\Leftrightarrow x^3-1-x^3+4x=5\)
\(\Leftrightarrow4x=6\)
hay \(x=\dfrac{3}{2}\)
d) Ta có: \(\left(x-2\right)^3-\left(x-3\right)\left(x^2+3x+9\right)+6\left(x+1\right)^2=15\)
\(\Leftrightarrow x^3-6x^2+12x-8-x^3+27+6\left(x^2+2x+1\right)=15\)
\(\Leftrightarrow-6x^2+12x+19+6x^2+12x+6=15\)
\(\Leftrightarrow24x=-10\)
hay \(x=-\dfrac{5}{12}\)
tìm x biết:
a) x2-2x+1=25
b) (5x+1)2-(5x-3)(5x+3)=30
c) (x-1)(x2+x+1)-x(x+2)(x-2)=5
d) (x-2)3-(x-3)(x2+3x+9)+6(x+1)2=15
a,\(< =>\left(x-1\right)^2-5^2=0< =>\left(x-1-5\right)\left(x-1+5\right)=0\)
\(< =>\left(x-6\right)\left(x+4\right)=0=>\left[{}\begin{matrix}x=6\\x=-4\end{matrix}\right.\)
b,\(< =>25x^2+10x+1-25x^2+9-30=0\)
\(< =>10x-20=0< =>10\left(x-2\right)=0< =>x=2\)
c,\(< =>x^3-1-x\left(x^2-4\right)-5=0\)
\(< =>x^3-1-x^2+4x-5=0< =>4x-6=0< =>x=\dfrac{6}{4}\)\(d,< =>\left(x-2\right)^3-x^3+3^3+6x^2+12x+6-15=0\)
\(< =>x^3-6x^2+12x-x^3+6x^2+12x+10=0\)
\(< =>24x+10=0< =>x=-\dfrac{5}{12}\)
a: Ta có: \(x^2-2x+1=25\)
\(\Leftrightarrow\left(x-4\right)\left(x-6\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=4\\x=6\end{matrix}\right.\)
b: Ta có: \(\left(5x+1\right)^2-\left(5x-3\right)\left(5x+3\right)=30\)
\(\Leftrightarrow25x^2+10x+1-25x^2+9=30\)
\(\Leftrightarrow10x=20\)
hay x=2
c: Ta có: \(\left(x-1\right)\left(x^2+x+1\right)-x\left(x+2\right)\left(x-2\right)=5\)
\(\Leftrightarrow x^3-1-x\left(x^2-4\right)=5\)
\(\Leftrightarrow x^3-1-x^3+4x=5\)
\(\Leftrightarrow4x=6\)
hay \(x=\dfrac{3}{2}\)
Bài 5:Tìm các số nguyên x, biết:
a)( 2 x - 5 ) + 17 = 6
b)10 - 2 ( 4 - 3x ) = - 4
c)24 : ( 3 x - 2 ) = - 3
d)5 - 2 x = - 17 + 12
\(a,\left(2x-5\right)+17=6\\ \Rightarrow2x-5=-11\\ \Rightarrow2x=-6\\ \Rightarrow x=-3\\ b,10-2\left(4-3x\right)=-4\\ \Rightarrow2\left(4-3x\right)=14\\ \Rightarrow4-3x=7\\ \Rightarrow3x=-3\\ \Rightarrow x=-1\\ c,24:\left(3x-2\right)=-3\\ \Rightarrow3x-2=-8\\ \Rightarrow3x=-6\\ \Rightarrow x=-2\\ d,5-2x=-17+12\\ \Rightarrow5-2x=-5\\ \Rightarrow2x=10\\ \Rightarrow x=5\)
a: =>2x-5=-11
=>2x=-6
hay x=-3
b: =>2(4-3x)=14
=>4-3x=7
=>3x=-3
hay x=-1
c: =>3x-2=-8
=>3x=-6
hay x=-2
a) 2x-5+17=6
2x+12=6
2x=12-6
2x=6
x=6:2
x-3
b) 10-8+6x=-4
2+6x=-4
6x=-4-2
6x=-6
x=(-6):6
x=-1
c) 3x-2=24:(-3)
3x-2=-8
3x=-8+2
3x=-6
x=-6:3
x=-2
d) 5-2x=-5
-2x=-5-5
-2x=-10
x=-10:(-2)
x=5
Tìm x biết:
a, 16x² – 9(x + 1)²= 0
b, x2 (x – 1) – 4x2 + 8x – 4 = 0
c, x(2x – 3) – 2(3 – 2x) = 0
d, (x – 3)(x² + 3x + 9) – x(x + 2)(x – 2) = 1
e, 4x² + 4x – 6 = 2
f, 2x² + 7x + 3 = 0
e: ta có: \(4x^2+4x-6=2\)
\(\Leftrightarrow4x^2+4x-8=0\)
\(\Leftrightarrow\left(x+2\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-2\\x=1\end{matrix}\right.\)
f: Ta có: \(2x^2+7x+3=0\)
\(\Leftrightarrow\left(x+3\right)\left(2x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-3\\x=-\dfrac{1}{2}\end{matrix}\right.\)